NEW TECHNOLOGIES iN RECONSTRUCTIVE SURGERY OF INJURIES AND CICATRICIAL STENOSES OF TRACHEA - E. B. Topolnitskiy; A. V. Kvasov; E. I. Belikov; N. A. Shefer; G. Ts. Dambaev (Acta Biomedica Scientifica)
The results of treatment of 9 patients with mechanical injury of trachea and of 22 patients with cicatricial stenoses of trachea are presented, in this article. 18 patients had. staged, reconstructive and plastic operations at the cicatricial stenosis, 2 patients had. endoscopic recanalization of tracheal lumen and. 2 patients had. sleeve resection of trachea with, anastomosis. An. original medical complex including argon-plasmatic, cryosurgical and. lymphotropic technologies. In all cases we managed, to recover respiratory tract integrity and. to provide adequate breath through, natural respiratory tract.